228k views
5 votes
Find the derivative by using product rule and distribution
pls help quickly and show work ​

Find the derivative by using product rule and distribution pls help quickly and show-example-1

1 Answer

4 votes

Answer:

Below

Explanation:

First method:

● f(x)= (x^3-2x+1)×(x-3)

● f'(x)= (x^3-2x+1)' ×(x-3) + (x^3-2x+1)×(x-3)'

●f'(x)= (3x^2-2)×(x-3) + (x^3-2x+1) × 1

●f'(x) = 3x^3-9x^2-2x+6 + x^3-2x+1

● f'(x)= 4x^3-9x^2-4x+7

■■■■■■■■■■■■■■■■■■■■■■■■■■

Second method:

●f(x) = (x^3-2x+1)×(x-3)

●f(x) = x^4-3x^3 -2x^2+6x+x-3

●f(x) = x^4-3x^3-2x^2+7x-3

●f'(x) = 4x^3-9x^2-4x+7

We got the same result using both methods.

User RRTW
by
6.0k points